Lógica matemática no ensino fundamental como instrumento facilitador da aprendizagem no ensino da matemática - Silva, Nilton Miguel da (2012)
This research aims at analyzing and compare the performance of pupils, involved in activities that stimulate and develop logical reasoning. As a consequence of this objective: we want to develop educational materials to support the teacher in the proposed activities to develop logical reasoning and identify its benefits as a facilitator of mathematics teaching, in the opinion of students involved in the project, and suggest proposals to teaching / learning practices that enhance mathematics in public elementary schools. The empirical scope of this research is a public school in Duque de Caxias, Baixada Fluminense - RJ. The study group is composed of twenty eighth graders. Taking into account studies that show that the greatest obstacle is the use of a mechanical and repetitive methodology, which does not arouse students’ interest, not focusing on reflection and research, we believe that including activities that encourage logical reasoning as a facilitating tool to learn mathematics can contribute significantly to the improvement of mathematics teaching in basic education. Although you cannot assert that students participating in the project has "learned more mathematics", I can assure you that most students have prepared, may not be able to prove a theorem, but certainly are better prepared to understand your demonstration.